A "silent storm": uncovering the escalating crisis in mental healthcare for children and adolescents in Slovenia during and after the COVID-19 pandemic - Sanja Zupanič Mali; Sašo Karakatič; Maja Drobnič Radobuljac (BMC, 2024)
Abstract Aim Our aim was to assess the burden of children and adolescents' mental health problems on the Slovenian outpatient healthcare system before, during and after the pandemic. Methods In a retrospective analysis of healthcare indicators from 2008 to 2023, we analysed data from the National Institute of Public Health. Key domains included initial visits for mental and behavioural disorders (MBDs) to primary care for the population aged 0-19; the number of referrals to an initial assessment with a child and adolescent psychiatrist (CAP) at the secondary level for the population aged 0-17 along with the corresponding waiting times; and the number of urgent referrals for the population aged 0-17 to emergency mental health centres at the tertiary level. The calculations included rates per 1000 people. Descriptive statistics and diagrams were used to compare the data. Segmented linear regression analysis (SLR) was conducted on the primary healthcare data to identify the distinct temporal point indicating an increase. Results Comparing the average rates of the 2020-2022 period to those of the 2018-2019 period, there was a 20% increase in initial visits to primary care, a 23% increase in the referral rate to a CAP at the secondary level, and a 41% increase to the tertiary level of care. In secondary care, a four- to sevenfold increase in waiting times for the initial CAP assessment was observed between 2019 and 2023. The incidence of initial visits to primary healthcare services for MBD increased from 2008 to 2019 (average annual growth rate of 4.5%). The average annual growth rate for the 2020-2022 period tripled to 13.9%. The SLR showed that the trend of accelerating growth could have begun in 2017 for the 0-5 age group and possibly for the 15-19 age group as well. Conclusions After the initial decline in 2020, all levels of the Slovenian healthcare system faced an increased burden of MBD in children and adolescents from 2021 to 2022 compared to pre-pandemic levels. Nevertheless, a portion of this increase aligns with longitudinal growing trends from 2008 onwards. Tackling the crisis requires urgent national action, significant improvement in organization, and investments in mental health.